Visible-light-induced photoelectric gas sensing to formaldehyde based on CdS nanoparticles/ZnO heterostructures - Zhai, J.; Wang, D.; Peng, L.; Lin, Y.; Li, Xin Yong; Xie, T. (Elsevier, 2010)
A visible-light-induced gas sensing element based on the heterostructures of CdS nanoparticles (NPs)/ZnO microcrystals has been successfully developed. Commercial ZnO microcrystals were coated with CdS nanoparticles by a sonochemical method to form the heterostructures. Compared with native CdS NPs, the as-obtained CdS NPs/ZnO showed enhanced photocurrent intensity. And the heterostructures-based element exhibited an excellent performance of photoelectric gas sensing to formaldehyde induced by visible-light. Moreover, the photocurrent intensity and sensitivity to formaldehyde were controllable by tuning the amount of CdS NPs attached on the surface of ZnO microcrystals. A possible explanation on the sensing mechanism has been proposed. In addition, the gas sensing element possessed good reproducibility. Our results demonstrate that the heterostructures of CdS NPs/ZnO is an efficient and promising material for visible-light-induced photoelectric gas sensors working at room temperature. © 2010 Elsevier B.V. All rights reserved.